Conceptual Density Functional Theoretical Investigation of the Corrosion Inhibition Efficiencies of Some Molecules Containing Mercapto (-SH) Group - Kaya, Savas; Tüzün, Burak; Kaya, Cemal (Current Physical Chemistry, 2017)
Objective: In the present study, corrosion inhibition efficiencies of some molecules containing mercapto group (-SH) such as mercaptopryimidine (MP), 6-mercaptonicotinic acid (6-MN), thiophenol (TP), 3-mercaptobenzoic acid (3-MB), mercaptoacedic acid (MAA), mercaptopropionic acid (MPA) were investigated. Method: All calculations related to these molecules were performed in gas phase and at various level of B3LYP and HF method using Gaussian package program. Conclusion: As a result of examinations made considering quantum chemical parameters such as chemical hardness, electronegativity, chemical potential HOMO-LUMO energy gap (ΔE), it was suggested that 3-mercaptobenzoic acid (3-MB) is the best corrosion inhibitor among molecules considered in the study.
Keywords: corrosion inhibitors